STUDENT WORKSHEET BASED on PROBLEM ASSISTED by COMPUTER SIMULATION on STUDENTS CRITICAL THINKING SKILLS - Mariati Purnama Simanjutak; Nurliana Marpaung; Juniar Hutahaean; Berta Masrifa Panggabean; Chatarina M.S Purba; Azmi Mustafa (Jurnal Pendidikan Fisika, 2019)
The purpose of this study was to determine the increase of students' critical thinking skills in learning by using Student Worksheets (LKS) assisted by computer simulations. The worksheet used was problem based and contained questions that explore critical thinking skills. This type of research was a quasi experimental of two groups pretest-posttest design. The population of this study was all students of class X Semester I of SMA Negeri 9 Medan, which consisted of seven classes with the number of students was 243 students. The participants of this study consisted of 2 classes which used cluster random sampling technique. The first class was class of X MIA 2, 36 students, as an experimental which was treated by using student worksheets problem-based assisted by computer simulation. The second class was class X MIA 3, 32 students, as a control class which was treated by conventional learning using. The instrument used was a critical thinking test of 10 questions in the form of problem-based description. Based on the results of different tests, this study obtained significant differences on students 'critical thinking skills by using problem-based worksheets assisted by computer simulations. In other words the implementation of learning by using problem-based student worksheets was better in increasing students' critical thinking skills than conventional learning. Percentage increase in N-gain of critical thinking experimental class 64% and control class 43%, respectively - medium category.